Policy Allocation for Settlement Development Using Simple Allocation Matrix Rules and Geographic Information System - Litasari, Ulfah Choerunnisa Nurul; Widiatmaka, Widiatmaka; Munibah, Khursatul; Machfud, Machfud (Frontiers in Environmental Science, 2022)
The settlement growth is potentially increased by the rural-to-urban perspective change due to the new era of aerotropolis in Kulon Progo. Land-use planning evaluation is required, especially settlement, which has a significant impact on the environment. However, land-use evaluation studies are currently focused on conforming analysis of official land-use planning (OLUP) toward existing or predicted land use partially or in combination with the performance assessment unit. Consequently, it affects the quality of policy products by disregarding crucial considerations of diverse conditions at points of time and aspects of ideality, reality, and regulation. Therefore, the objective of this study was to design a comprehensive policy allocation for settlements using a matrix allocation rule that integrates conformity and performance analysis in three aspects of planning simultaneously. Land allocation was proposed using a geographic information system (GIS) of land capability, settlement suitability, and agricultural and forest land protection. The current land use/land cover (LULC) was classified using visual interpretation of SPOT 7 satellite imagery and a multi-layer perceptron neural network (MLPNN) to predict the LULC in 2035. The result indicated that the stock of land allocation for settlement development is sufficient to meet the demands in 2035. However, there is a problem in the settlement distribution pattern in which 64.3% of existing settlements are located in non-recommended allocation. That number is predicted to increase by 1,145.8 ha. Land-use control instruments need to be conducted to prevent extensive settlement growth in non-recommended allocation. Conversely, zoning allocation should be directed to trigger the growth of settlements in recommended allocation.